Studies on Experimentally Induced Hypercoagulable State in Rabbits - Izak, G; Galewsky, K (Thrombosis and Haemostasis, 1966)
The theory of the dynamic equilibrium in vivo between the opposing functions of the coagulation and fibrinolytic mechanisms was tested in rabbits with artificially induced hyper- and hypocoagulable states.When repeated estimations of the various clotting and fibrinolytic constituents were performed simultaneously with the determination of the disappearance rate of I131 labeled fibrinogen, thromboplastin induced hypercoagulable state could be monitored. Measuring the same parameters, interference with the coagulation system by the use of anticoagulants was found ineffective concerning the coagulation and fibrinolytic systems. Furthermore, the latter procedures were unable to modify the pattern of changes when employed in animals with artificially induced hypercoagulable state.The data presented militate strongly against the dynamic equilibrium hypothesis as suggested by several investigators.